Rising dissolved organic carbon concentrations in coastal waters of northwestern Borneo related to tropical peatland conversion - Sanwlani, Nivedita (2022)
Southeast Asia's peatlands are considered a globally important source of terrigenous dissolved organic carbon (DOC) to the ocean. Human disturbance has probably increased peatland DOC fluxes, but the lack of monitoring has precluded a robust demonstration of such a regional-scale impact. Here, we use a time series of satellite ocean color data from northwestern Borneo to show that DOC concentrations in coastal waters have increased between 2002 and 2021 by 0.31 μmol liter-1 year-1 (95% confidence interval, 0.18 to 0.44 μmol liter-1 year-1). We show that this was caused by a ≥30% increase in the concentration of terrigenous DOC and coincided with the conversion of 69% of regional peatland area to nonforest land cover, suggesting that peatland conversion has substantially increased DOC fluxes to the sea. This rise in DOC concentration has also increased the underwater light absorption by dissolved organic matter, which may affect marine productivity by altering underwater light availability.